Determinants of port centrality in maritime container transportation. (November 2016) - Wang, Yuhong; Cullinane, Kevin
Highlights: Freeman's degree, closeness and betweenness centrality measures are applied to ports. Available shipping capacity and foreland market coverage are accounted for. Foreland market coverage has a strong influence on demand and closeness centrality. High scoring ports in betweenness centrality have high degree and closeness measures. Available shipping capacity and foreland market coverage most influence estimates. Abstract: This paper adapts Freeman's measures of degree, closeness and betweenness centrality and applies them to assessing: port centrality in relation to direct connectivity; accessibility to all ports in the network (direct and indirect routes) and; as an intermediary between other ports. An additional parameter added to the formulae ensures that the relative importance of available shipping capacity and foreland market coverage are also accounted for. Validation of this adapted measure is provided by the results obtained from an empirical application. These reveal that foreland market coverage exerts a particularly strong influence on a port's demand and closeness centrality.